Amending and Extending Referendum Ballots : Innovations in Referendum Literature and Practice - Wagenaar, Charlotte C.L. (Politics of the Low Countries, 2023)
A dominant criticism in the democratic innovations literature with respect to referendums is their tendency to promote a single proposal that voters can only accept or reject. The inability to make compromises can aggravate rather than solve policy conflicts (e.g. Altman, 2018; Morel, 2018a). It also provides the author of the ballot proposal and the actor initiating the referendum – which may be the same or two different actors – with significant influence over referendum process and outcome (e.g. Hug & Tsebelis, 2002; Jäske & Setälä, 2019; Wagenaar, 2021). There are, however, ways in which referendum processes can be adapted to comprise improved or additional policy proposals, which are more in line with societal preferences than the sometimes narrow interests of the initiator or the author of the initial proposal. This article reviews innovations to referendum processes that deviate from the traditional binary referendum on a predetermined proposal. Such innovations have been proposed by various This article presents them alongside one another and reviews their applicability for referendums in the low countries, where referendums are being held predominantly at the local level and where offering a real choice to voters and interpreting how to adapt rejected legislation regularly poses challenges to local decision-making. At the same time, the decentralised level lends itself well to experimentation with alternative referendum procedures in diverse contexts and on diverse topics, and the proximity to citizens facilitates following up on how legislators deal with citizen input (Verhulst & Nijeboer, 2007). The proposed innovations in referendum initiation and ballot formulation described in this article are compared with empirical examples as well as suggestions emerging from society in the low countries aimed at increasing the constructive value of referendum processes as a tool of citizen participation.